The Influence Of Service Quality, Product Quality, And Brand Image On Purchasing Decisions: Case Study of Nako Kebon Jati Bogor Coffee - Sulistiono, Sulistiono; Maghfirah, Annisah Al; Astrini, Danti (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the effect of Service Quality, Product Quality, and Brand Image on Purchasing Decisions of Nako Kebon Jati Coffee. The number of samples is 385 respondents. The sampling method used is purposive sampling. The data analysis method used is Multiple Regression Analysis to find out whether service quality, product quality, and brand image can influence purchasing decisions on Kebon Jati Nako coffee. Data Processing Using the Statistical Package for the Social Science (SPSS). From the research results, the following data were obtained: (1) Service quality has a positive and significant effect on purchasing decisions for Kebon Jati Nako coffee. (2) Product quality has a positive and significant effect on purchasing decisions for Kebon Jati Nako Coffee. (3) Brand Image has a positive and significant effect on Purchasing Decisions. (4) Service Quality, Product Quality, and Brand Image simultaneously have a positive and significant effect on Purchasing Decisions. Keywords: Service Quality, Brand Quality, Brand Image, Purchasing Decision